Probe-based Confocal Laser Endomicroscopy for In Vivo Assessment of Histological Healing in Ulcerative Colitis: Development and Validation of the ENHANCE Index. (17th December 2020) - Rahmi, Gabriel; Coron, Emmanuel; Perrod, Guillaume; Levy, Michael; Moreau, Jacques; Moussata, Driffa; Perez-Cuadrado-Robles, Enrique; Chupin, Antoine; Quénéhervé, Lucille; Bourreille, Arnaud; Marchal, Aude; Cellier, Christophe; et al.
Abstract: Background and Aims: Histological healing may represent the ultimate therapeutic goal in ulcerative colitis [UC], but it requires biopsies. Our aim was to develop a non-invasive index able to assess histological disease activity in ulcerative colitis, using probe-based confocal laser endomicroscopy [pCLE]. Methods: One hundred patients with quiescent UC were prospectively included in five French centres. After fluorescein intravenous injection, during colonoscopy, the colorectal mucosa was analysed by white light imaging and pCLE, and then biopsied in different locations. Five endoscopists performed central reading of pCLE images blinded to clinical, endoscopic, and histological data. One expert pathologist performed a central histological reading [Nancy index: gold standard]. Univariate and multivariate analyses were performed to identify the endomicroscopic items associated with the presence of histologically active disease. Results: Over 1000 pCLE videos sequences performed in 100 UC patients in endoscopic remission [Mayo 0 and 1] were evaluated. We observed that vessel diameter >20 µm, dilated crypt lumen, fluorescein leakage, and irregular crypt architecture were statistically associated with histologically proven inflammation according to the Nancy index. Hence, we built a pCLE index of mucosal inflammation with overall accuracy of 79.6% and overall sensitivity and specificity of, respectively, 57.8% and 82.8%. Negative predictive value, especially when a pCLE index ≤1 was observed, was high [93.1%]. Conclusions: Using a robust methodology, large vessel diameter, dilated crypt lumen, fluorescein leakage, and irregular crypt architecture are reliable endomicroscopic items defining the ENHANCE index for real-time assessment of histological disease activity in UC.